An innovative food system approach to diversifying protein intake: Protein‐I: Shared Island sustainable healthy nutrition. Issue 4 (27th November 2022) - Brennan, Lorraine; O'Gorman, Aoife; Barth, Susanne; Cadden, Trevor; Dean, Moira; Doohan, Fiona; Henchion, Maeve; McIvor, Ronan; McNulty, Breige; O'Donoghue, Cathal; O'Reilly, Seamus; Rafferty, Joseph; et al.
Abstract: There is a need to transform our current food system if we are to feed the rapidly expanding global population while maintaining planetary health. Within the island of Ireland, there is an urgent need to diversify the foods that currently contribute to our populations' protein intake. A Shared Island Innovative Food System approach is required to achieve this in a manner that is sustainable and provides benefits to producers, consumers and other supply chain participants. The Protein‐I project employs such an approach, with the paradigm focusing on production of plant food through to human health, while paying particular attention to the development of the rural bioeconomy. Using an interdisciplinary approach, the team will develop strategies to maximise sustainable plant protein production in a traceable/transparent fashion and assess the impact of changes to existing value chains and the development of new value chains for the rural economy. A smart supply chain technology solution tailored to the needs of the agri‐food industry will be developed and tested. Additionally, we will co‐design consumer‐led approaches to diversify plant protein intake, model the impact of changes at the population level and perform human interventions to demonstrate efficacy in terms of achieving adequate nutrition and improved health. Comprehensive engagement with stakeholders is embedded throughout the whole project to embrace the multi‐actor approach. Overall, the project will be a key step towards future‐proofing our food system on the island of Ireland and moving towards protecting planetary and population health, within the context of a just transition.